2006
DOI: 10.1007/s10811-006-9045-7
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Various Seaweed-Based Diets and Formulated Feed on Growth Rate of Abalone in a Land-Based Aquaculture System

Abstract: The effects of different diets on growth in the cultured South African abalone, Haliotis midae (Linnaeus), was investigated. Growth of juvenile Haliotis midae was monitored on a commercial abalone farm over a period of 9 months in an experiment consisting of 9 treatments with 4 replicates (n = 250 individuals per replicate). The treatments were: fresh kelp (Ecklonia maxima) blades (seaweed control); Abfeed R (formulated feed control); kelp + Abfeed R ; dried kelp pellets; dried kelp blades; dried kelp stipes; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(57 citation statements)
references
References 15 publications
5
46
0
3
Order By: Relevance
“…Similarly, MA common ly used as feed in wild did not produce the optimal performance of abalone (Lee, 1998;Cho et al, 2006;Kim et al, 1998;Naidoo et al, 2006;Cho et al, 2008;Gracia-Esquivel & Felbeck, 2009;Dang et al, 2011;Myung et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MA common ly used as feed in wild did not produce the optimal performance of abalone (Lee, 1998;Cho et al, 2006;Kim et al, 1998;Naidoo et al, 2006;Cho et al, 2008;Gracia-Esquivel & Felbeck, 2009;Dang et al, 2011;Myung et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the lower levels of these transaminases observed in the rats treated with the seaweed extract after exposure to the toxin. The tendency of other marker enzymes to return towards a near-normalcy in the H. muciformis treated rats was a clear manifestation of anti-hepatotoxic effect due to the presence of sulphated polysaccharides and vitamin C in the seaweed extract (Naidoo et al 2006). The results were comparable to sylimarin.…”
Section: Discussionmentioning
confidence: 67%
“…By trapping the oxygen related free radicals, the H. muciformis extract could hinder their interaction with the polyunsaturated fatty acids and would abolish the enhancement of lipid peroxidative processes (Upadhyay et al 2001). It is well documented that flavonoids and glycosides are strong antioxidants (Natarajan et al 2006). The antioxidant principles from the natural marine resources are multifaceted in their effects and provide enormous scope in correcting the imbalance through regular intake of a proper diet.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies (Owen et al 1984, Day and Fleming 1992, Fleming 1995a, Simpson and Cook 1998, Naidoo et al 2006, Dlaza et al 2008) have shown the benefits of variability in the diets (e.g. mixed and rotational diets) of abalone, no studies exist to show the benefit of feeding farm-grown macroalgae over that of their wild counterparts.…”
Section: Discussionmentioning
confidence: 99%